Integrating E-Commerce, Influencers, UGC, and Personal Shoppers to Drive Asian MSME Internationalization - Rizkita, Marsya Aulia; Sudarmiatin; Pratikto, Heri (Universitas Kadiri, 2026)
The prevailing narrative in international business research has long positioned Micro, Small, and Medium Enterprises (MSMEs) as structurally disadvantaged actors in global trade—constrained by the dual liabilities of smallness and foreignness and largely dependent on gradual, resource-intensive market entry strategies. This systematic literature review challenges the adequacy of that framing in the Asian context. Drawing on 60 peer-reviewed sources published between 2018 and 2026, and adhering to PRISMA guidelines, we argue that a synergistic digital ecosystem—comprising cross-border e-commerce (CBEC) infrastructure, influencer marketing, user-generated content (UGC), and human-mediated personal shopper networks—has fundamentally restructured the internationalization calculus for MSMEs across the region. These four drivers do not operate independently; they form a co-evolving network in which each mechanism amplifies the signal and mitigates the risk posed by the others. E-commerce platforms expand market reach and improve supply chain performance; influencers and UGC build consumer trust and brand credibility; personal shoppers bridge cultural and cross-border gaps with personalized service and embedded social intelligence. Critically, we identify a structural divergence between two dominant regional models: China’s high-tech, AI-driven paradigm—characterized by super-app ecosystems, virtual influencers, and algorithmic personalization—and Southeast Asia’s high-touch model, which privileges authenticity, community trust, and human mediation. Both pathways achieve international reach, but they do so by leveraging fundamentally different types of capital. This review also engages seriously with the dark side of digital transformation: platform dependency, algorithmic opacity, the unmeasurable influence of ‘dark social’ channels, structural digital literacy deficits, influencer scandals, and frugal innovation as a counter-strategy. These are not peripheral concerns—they are systemic vulnerabilities that constrain the sustainability of digitally driven internationalization. The paper concludes with a research agenda oriented toward Industry 5.0 frameworks, AI ethics, and longitudinal methodologies capable of capturing the long arc of digital resilience.